Theoretical and Practical Problems of Acquiring Competence in Intercultural Communication in Polish, English and Russian = Teoretyczne i praktyczne aspekty nabywania kompetencji w zakresie komunikacji międzykulturowej w języku polskim, angielskim i rosyjskim - Kuzio, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Human beings have a great need to be with people who are similar to themselves. This is because they share the same ways of doing things, the same values, as well as function by similar rules. When one is with people who tend to be similar to you, the ways of doing things just seem like common sense. However, sometimes one realizes that the situation appears to be more complex.
Keywords: intercultural communication; intercultural competence; discourse; deception inlanguage; komunikacja międzykulturowa; kompetencje międzykulturowe; dyskurs; kłamstwo